Effects of toluene-di-isocyanate microcapsules on the frost resistance and self-repairing capability of concrete under freeze-thaw cycles. (December 2021) - Du, Wei; Liu, Quantao; Lin, Runsheng
Abstract: Concrete buildings used in severe cold regions are susceptible to freeze-thaw damage, resulting in internal cracking and surface spalling of concrete. Microcapsules can self-repair concrete cracks and improve the durability of concrete. This paper focuses on the effects of toluene-di-isocyanate (TDI) microcapsules on the frost resistance and self-repairing capability of concrete under freeze-thaw cycles. The mass and mechanical properties of concrete were measured before and after freeze-thaw cycles. The pore size distribution and microstructure of the concrete were characterized using nuclear magnetic resonance and scanning electron microscopy (SEM). The mechanical properties and permeability of freeze-thaw damaged concrete were assessed by compressive strength tests and rapid chloride migration (RCM) tests after self-repairing. The frost resistance and self-repairing capability of concrete containing microcapsules were also evaluated by ultrasonic test. The results showed that the concrete containing nano-SiO2 /paraffin/PE wax encapsulated TDI microcapsules (CON3) had better frost resistance and self-repairing capability than the concrete containing other microcapsules. After 100 freeze-thaw cycles, the mass loss rate and compressive strength loss rate of CON3 were only 1.63% and 13.6%, respectively. After 7 d of self-repairing, SEM images showed that repairing products with network structure appeared in the pores of CON3, which improved the microstructure of concrete. The harmful pores proportion, compressive strength recovery rate, chloride diffusion coefficient recovery rate, maximum amplitude and dominant frequency maximum amplitude of CON3 were 47.8%, 96.9%, 84.6%, 77.99 mV and 8.37 mV, respectively. Highlights: After adding microcapsules, the frost resistance of concrete was improved. Microcapsules can significantly improve the self-repairing capability of concrete subjected damaged by freeze-thaw. Compared with CON1 and CON2, CON3 has better self-repairing capability after freeze-thaw damage.